KAJIAN FURNITURE PADA INTERIOR RUANG KELAS PENYANDANG AUTIS - Anggi Dwi Astuti (Narada : Jurnal Desain dan Seni, 2019)
Autism sufferers have a disruption to social interaction, communication, imagination with repetitive behavior patterns and resistance (not easy to adjust) to the environment and routine in general. This disorder in social interaction issue causes autism sufferers to look strange and different from other people. Autistic sufferers must be given the widest opportunity to develop their potential by creating a special forum that aims to get special education for children with special needs such as autistic children. One form of therapy offered is one on one method. Designing the right layout and using the right furniture can provide an autistic child to be relaxed and comfortable to undergo the therapy and learning. Objectives to be achieved in the design of children’s autism desk is to help children and mentors carry out the therapeutic process by considering several factors namely safety, comfort, and optimization of the therapeutic process. In the process with the existing planning and design methods among them; Data collection, design concepts, design alternatives, design development of selected alternatives, and final design, the final result of the design of this autistic children’s desk is designed to function as well as a means of sensory and motor therapy of children